Virtual Visual Arts Integration and Biology: More Favor or Challenging for Emergent Bi/Multilingual High Schoolers - Aghasafari, Sahar (Journal of Interdisciplinary Studies in Education, 2023)
As educators, we are becoming increasingly aware that delivering effective education is likely to change after the coronavirus pandemic. As a result, we have an opportunity to frame teaching differently and bring innovation to the forefront. In doing so, educators explored online tools, creative ways to connect with students, and found new ways to teach. Using an exploratory case study methodology and working within a theoretical framework of Symbolic Interactionism (SI), I investigated how did virtual teaching visual arts integration and biology more favour or challenging for emergent bi/multilingual high schoolers. The lesson was implemented titled Using Depiction to Illustrate the Interdependent Functions of a Plant Cell. I implemented a series of visual arts integration activities with ten ninth-grade emergent bi/multilingual students at a mid-sized high school located in the south-eastern region of the United States. Research activities took place, via zoom, in a communication skills class. Findings reveal that emergent bi/multilingual students can benefit from face-to-face classes because they get more practice speaking and benefit from their teacher’s advice on their tasks, but more flexible class times and delivery methods may help students meet the many challenges created by the need to help provide for their families.